Music & the British military in the long nineteenth century - Herbert, Trevor 1945-; Barlow, Helen 1967- (Oxford University Press, 2013)
This study examines the relationship between the British military as a sponsor of music and musicians within wider aspects of music history during the nineteenth century. While the focus is on Britain, it also deals directly or by implication with other European countries and the USA. Throughout the period the military was by far the largest employer of musicians and generator of the most widely dispersed musical networks. Consequently it was essential to the commerical infrastructures of music